(untitled) (Widyadari, 2024)
This study aims to test the impact Human Relations, Social Work Environment AndleadershipOn Employee Performance at Sanjiwani Hospital in Gianyar Regency with the main theory of Organizational Behavior and Human Resources. The qualitative research method used a questionnaire with 58 respondents and four hypotheses which were processed using SPSS version 24. The results of the research stated 1. Leadership (X1) has a positive and significant effect on the performance of Employees at the Sanjiwani Gianyar Hospital, 2. Social Work Environment (X2) has a positive and significant effect on the performance of employees at the Sanjiwani Gianyar Hospital, 3.Human Relations (Z) negative effectand not significant to the performance of employees of the Sanjiwani Gianyar Hospital in Gianyar Regency, 4.Human Relationsable to mediate between leadership and social work environment on the performance of employees at sanjiwani hospital. Implications: Leadership Impact Social Work Environment and Human Relationson Moderate Employee Performance